Adenoid cystic carcinoma of the external auditory canal with metastasis to the cerebellopontine angle mimicking vestibular schwannoma: a case report and literature review - Guo, Zhifei; He, Jie; Zhang, Xiangyu; Xu, HaiYan; Zhao, Bing; Cao, Wei (Frontiers in Oncology, 2026)
Purpose/aimAdenoid cystic carcinoma (ACC) of the external auditory canal (EAC) is a rare malignancy with a propensity for perineural invasion and distant metastasis. Its metastasis to the cerebellopontine angle (CPA) has not been previously documented. This case report presents a unique instance of CPA metastasis from EAC ACC, which mimicked vestibular schwannoma. We also review pertinent literature to enhance awareness of this atypical presentation.Case reportWe present the case of a 62-year-old male with CPA metastatic ACC who experienced right facial paralysis and hearing loss for more than 5 years. The patient underwent a surgical resection of the ACC of the right EAC in the Otolaryngology, Head and Neck surgery department 10 years ago. The postoperative recovery was good, and symptoms of right facial paralysis began to appear in the fourth year after surgery. Reexamination via head Computed Tomography (CT) and Magnetic resonance imaging (MRI) revealed no local recurrence or distant metastasis. Over subsequent years, the patient’s symptoms of facial paralysis gradually worsened, and discomfort, such as eyelid ptosis, decreased vision, and hearing loss, occurred, MRI of the head revealed a cystic lesion located in the right CPA. On March 19, 2025, the patient underwent retrosigmoid craniotomy, the tumor was found to be located in the CPA, penetrating into the Internal auditory canal (IAC), with a solid and tough texture, abundant blood vessels, clear boundaries. Gross total resection was achieved. The patient was discharged on the 9th postoperative day with good recovery and without any new neurological dysfunction. Histopathological examination revealed a diagnosis of ACC. One month after surgery, the patient received adjuvant chemoradiation and was disease-free at 8-month follow-up after the second surgery.ConclusionsACC of the EAC with intracranial extension into the CPA is an exceptionally rare clinical entity that may radiologically mimic vestibular schwannoma. To our knowledge, this is the first such case reported in the literature. From this rare case, neurosurgeons should understand that malignant pathologies must be considered when diagnosing CPA masses, particularly when atypical features such as perineural spread are present.